2014
DOI: 10.11604/pamj.2014.19.394.5717
|View full text |Cite
|
Sign up to set email alerts
|

Benign breast lesions in Bayelsa State, Niger Delta Nigeria: a 5 year multicentre histopathological audit

Abstract: IntroductionThere has been no previous study to classify benign breast lesions in details based on histopathologically confirmed diagnosis in Bayelsa State, Nigeria. This study therefore aims to review all cases of benign breast lesions seen in all the three centres in Bayelsa State with histopathology services over a five year period for a comprehensive baseline data in our community for management, research and education.MethodsThis is a multicentre retrospective descriptive study based on histopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
5
11
1
Order By: Relevance
“…The pattern of breast diseases and their etiology varies among different countries and ethnic groups (Aslam et al, 2013).In this study the pattern of breast diseases among women attending breast diagnosing center in Erbil city /Iraq had been identified, thus nearly two thirds (63%) of them were diagnosed as benign breast diseases while 13.2% found to have breast cancer, these results were nearly similar to two studies conducted in Nigeria (Mayun, Pindiga, & Babayo, 2008;Uwaezuoke & Udoye, 2014) while other studies conducted in India (Rasheed et al, 2014) and Tanzania (Chalya et al, 2016) showed slightly higher proportions of both benign breast diseases; (80.7%), (80,4%) and that of breast cancer (22.2 %), (19.6%) respectively. This could be related to the demographic characteristics of the selected sample since only (17%) of the women in this study were above 50 years.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The pattern of breast diseases and their etiology varies among different countries and ethnic groups (Aslam et al, 2013).In this study the pattern of breast diseases among women attending breast diagnosing center in Erbil city /Iraq had been identified, thus nearly two thirds (63%) of them were diagnosed as benign breast diseases while 13.2% found to have breast cancer, these results were nearly similar to two studies conducted in Nigeria (Mayun, Pindiga, & Babayo, 2008;Uwaezuoke & Udoye, 2014) while other studies conducted in India (Rasheed et al, 2014) and Tanzania (Chalya et al, 2016) showed slightly higher proportions of both benign breast diseases; (80.7%), (80,4%) and that of breast cancer (22.2 %), (19.6%) respectively. This could be related to the demographic characteristics of the selected sample since only (17%) of the women in this study were above 50 years.…”
Section: Discussionsupporting
confidence: 83%
“…Gupta, Goyal, & Sharma, 2015), in Nigeria (45.6%) (Uwaezuoke & Udoye, 2014) and (52%) in a study done by (Naveen, Mukherjee, & Mahajan, 2013). While the second most common benign breast disease in this study found to be breast cyst (8.6 %), a study done in Africa (Femi, Nnaetio, & Ayedima , 2016) showed that breast cyst was the 5 th benign disease but with a proportion of (14.0%).…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Benign non proliferative lesions of the breast were the commonest lesions 159(74.0%) in females in our study. Of these lesions Fibroadenoma (76%),is the commonest benign non-proliferative lesion, mirrowing other Nigerian studies [14,[32][33][34][35][36]. Other benign lesions in the female breast in our study were Periductal mastitis, lipomas, fat necrosis, tubular adenoma, Juvenile papillomatosis, granulomatous mastitis, granulation tissue, benign phyllodes, acute mastitis, lymphocytic mastitis, granular cell myoblastoma, lactating adenoma and myofibroblastoma all of which account for less than 30 percent.…”
Section: Discussionsupporting
confidence: 80%
“…Understanding indicators of HMG in middle-aged women play an important part in public health and clinical implications. Researches have identified multiple risk factors for HMG 3 , such as late age at menopause 4,5 , nulliparity 4,5 , lacking breastfeeding 6 , high-level education 7 and family history of breast cancer 8 . Nevertheless, etiology of HMG remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%